Printed high mobility AMOS thin film transistors - Evanniles, Edbert (Nanyang Technological University, 2020)
The report is done to investigate the effects the addition of gallium to the IZO thin film transistor and hydrogen peroxide to the IGZO solution processed thin film transistor. One major issue of the IZO Thin film transistor is with the instability of the device caused by the formation of vacancy defects, which causes performance issues with the device In this report, we added Gallium to form IGZO TFTs, and the mobility of the IZO in comparison with the IGZO TFTs has increased from 5.03 cm2/V.s to 6.98 cm2/V.s and the threshold voltage from -2.67 volts to -2.02 volts. With the addition of hydrogen peroxide to the IGZO TFTs, the mobility of the IGZO device has increased from 6.98 cm2/V.s to 8.04 cm2/V.s and the threshold voltage from -1.68 volts All the results above suggests that the addition of gallium and the addition of hydrogen peroxide results in a improvement in the device parameters